Historical аnd Ethnological Characteristics оf Ethnic Romanians оf Bessarabia - Sokolova, Mariia (Journal of Danubian Studies and Research, 2023)
The aim of this paper is to study the main stages of the development and settlement of the territory of Southern Bessarabia by ethnic Romanians, as well as the peculiarities of the formation of Romanian folk culture. In order to achieve this aim, it is necessary to solve the following tasks: to study ethnogenetic and demographic processes in the formation of the folk culture of the Romanians of Southern Bessarabia, to identify the influence of other ethnic groups on Romanian national self-awareness. In this study, a set of research methods is used: genetic and historical method; formal and typological method; functional method. The actuality of the research lies in the fact that for the first time the folk culture of the Romanian population of Bessarabia is considered as a result of the interaction of integration, adaptation and transformation processes that formed the multiethnic community of the Romanian ethnic group. The paper examines the state of two parallel vectors – «Moldovanism» and «Romanism» – which define two identities, and also distinguishes two stages of Moldovan ethnogenesis: the formation of the Eastern Romanian ethnic community and the formation of the Moldovan nation itself. The study shows that the formation of the modern national-regional picture of the Bessarabian region is evidence not only of the long process of formation of the ethnogenesis of the Romanian-speaking population, but also of the life of representatives of other ethnic groups.